Regimes de visibilidade do corpo fragmentado e construção de sentido e interação na vídeoarte brasileira - Ribeiro, Regilene Aparecida Sarzi (2012)
The theme of this research is to build simulations of the fragmented body and its role as an operator of the meaning and interaction of the individual in the contemporary. The research objectives are: to analyze the role of the organization figurative and plastic, the thematization of the body, the figuration of the whole and the parts that link to different treatments of the subject and intervene in the narrative and discursive interactions, study of social meaning and visibility through the interactional relations arranged by the use of expressive audiovisual system, the description of the procedures enunciative, the apprehension of the individuals in interaction and processing a esthesic sense of body self and other. The methodological basis of the research is based on Discursive Semiotics of Algirdas Julien Greimas and his associates, in the Semiotics of Plastic Jean-Marie Floch, in the field of social interactions formalized by Eric Landowski Sociossemiótica and research in the semiotic Brazilian Ana Claudia de Oliveira on the expression sensitive to global enunciation of concreteness. The research corpus consists of four Brazilian vídeoartes produced between the years 1975 and 2002. The actors of utterances installed in the works prepared for analysis are artists belonging to the first and current generation of Brazilian vídeo, as Leticia Parente, a pioneer in the record of performing actions in the 1970s, and Nina Galanternick, Danillo Barata and Lia Chaia, recognized for experimentation and research of vídeo language. The vídeos have analyzed points in common, like the fact that the body of the creator as the enunciator and surfactant statement and closeness between some semantic categories, but differ in aesthetic treatment, plastic and audiovisual syncretism. Research shows the fragmented body as an operator in the sense vídeoartes and vídeo as a semiotic fact that it makes in the act, which gives you the power to capture in close proximity to the body effect and its enunciation of significant seizures of meaning. Of semiotic analysis comes to the operationalization of aesthesia, procedures and metonymic description of the effects of meaning generated in the interaction between the discursive body language, gestures and kinetic and audiovisual language. The study contributes to the area of communication, in that it presents original research, detailed and elaborate procedure of mediation between the metonymic, the part for the whole, interactive media and practices that expand the topic and offer referrals relevant to future studies on the convergence between art and media, art and communication